In Defense of the Iraqi Media – Between Fueling Conflict and Healthy Pluralism - Wollenberg, Anja; El Richani, Sarah; Jekta, Maral (Global Media Journal - German Edition, 2017)
Despite the occupation and ensuing war, Iraq has experienced the emergence of a truly pluralistic media landscape after the fall of the Baath regime in 2003. Today, media coverage of domestic affairs is characterized not only by pluralism but also by bias and partiality reflecting strong ties between political actors and media outlets. Accordingly, the Iraqi media are often ac-cused of fueling conflict and deepening the ethno-sectarian divide in society. Based on a qualitative frame analysis of Iraqi news bulletins, this study reveals that Iraqi media outlets provide indeed contesting frames on even the most divisive issues. Only the coverage of the armed war against IS is characterized by a non-pluralistic conformity among Iraqi channels that unequivocally focus on military successes against IS and jointly refrain from any criticism against the varied forces fighting IS in Iraq.